Effects of ultra-high pressure treatment on structure and bioactivity of polysaccharides from large leaf yellow tea. (1st September 2022) - Chen, Hao; Huang, Yuzhe; Zhou, Cancan; Xu, Tenglong; Chen, Xinyang; Wu, Qianzhen; Zhang, Kunfeng; Li, Yong; Li, Daxiang; Chen, Yan
Graphical abstract: Highlights: Ultra-high pressure (UHP) could change the primary and spatial structure of polysaccharides. UHP could enhance the content of uronic acid and the bioactivity of polysaccharides. UHP treatment was more efficient than Sevage's method in removing protein. Abstract: In this study, the changes of structure and bioactivity of polysaccharides from large leaf yellow tea (LYTP) were investigated under ultra-high pressure (UHP). Native yellow tea polysaccharide were treatmented with ultra-high pressure (200, 400 and 600 MPa) for 5 min to yield yellow tea polysaccharide including 200 MPa-LYTP, 400 MPa-LYTP and 600 MPa-LYTP. It was found that the monosaccharide composition of LYTP changed significantly after the ultra-high pressure treatment. The molecular weight (Mw) of 200 MPa-LYTP (from 563.6 to 11.7 kDa), 400 MPa-LYTP (from 372.2 to 11.8 kDa) and 600 MPa-LYTP (from 344 to 11.6 kDa) sharply decreased upon ultra-high pressure treatment compared with LYTP (771.5 kDa), coincidentally particle size was also significantly reduced for 200 MPa-LYTP (23.2 %), 400 MPa-LYTP (40.2 %) and 600 MPa-LYTP (25.9 %). The results of the scanning electron microscope showed that ultra-high pressure also changed the surface and spatial morphology of LYTP. LYTP after ultra-high pressure treatment (UHP-LYTP) could further ameliorate alcohol-induced liver injury in mice. In addition, UHP treatment can more efficiently remove protein than the Sevages method. With the gradual removal of protein, its hepatoprotective effect increased. These findings demonstrated that UHP treatment could change the primary structure and spatial structure of LYTP, increase the content of acidic polysaccharides, and improve its bioactivity.